PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) Â UNTUK MENINGKATKAN HASIL BELAJAR MENENDANG DENGAN KAKI BAGIAN DALAM SEPAK BOLA PADA SISWA KELAS V SDN KOMPLEK KENJERAN II SURABAYA - SARLAN, (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract In penjasorkes (physical, sport and art education) in SDN Komplek Kenjeran II Surabaya lesson of kicking by inner food have been performed yet the result not optimum. In previous lesson teacher used direct learning model with the limitation where teacher dominates in the process, lack of feedback, students become individualistic and had less cooperation. It was indicated by assessment that have been performed at grade V SDN Komplek Kenjeran II Surabaya, where 28 students or 80% had less criteria and 7 students had mark 70 or above or 20% had good criteria. Hence this research used cooperative learning model of student team achievement division (STAD) type which emphasized on learning in group and cooperation among group members. STAD learning is one of cooperative learning model using small groups that consist of 4-5 heterogeneous member, it is mixture of achievement level, gender, social and ethnicity background in hope that the learning can improve learning result. This research aimed to identify learning result improvement of kicking by inner foot using Student Teams Achievement Division (STAD) model in students at grade V SDN Komplek Kenjeran II Surabaya. This research was experimental research using class action approach or class action research (PTK). Subject of research was students at grade V SDN Komplek Kenjeran II Surabaya.  It was due to all problem were derived from this class. Number of students was 35 students with 20 males and 15 females. Research result was following: in cycle 1, 18 students or 51.42% were successful to surpass KKM and it was said that learning method implementation had not been completed. In cycle 2, 31 students or 88.57% were successful to surpass KKM. Since percentage was more than 75,00% it was determined as complete. For mean of kicking by inner foot, initial study resulted in 20% and the final study had 88,57%. Hence learning result improvement of kicking by inner foot before and after receiving Student Teams Achievement Division (STAD) method was 17.50%. Keywords: Class Action Research (PTK), Student Teams Achievement Division (STAD), kicking by inner foot in football.